Oncofetal HMGA2 as a key regulator of telomere stability through control of DNA topology - Dharshana, Ramani Priya (2018)
Faithful replication of the whole genome is fundamental to maintain the genome integrity. During this process, the replication forks may encounter various endogenous and exogenous factors that could lead to replication fork stalling. Telomeres in particular experience numerous replication and topological fork barriers due to its intrinsic nature characterized by repetitive DNA sequences, heterochromatin, and formation of DNA secondary structures; a consequence of TERRA transcription. These impediments present telomeres as ‘difficult-to-replicate’ regions in the genome necessitating both temporal and spatial barrier resolution, which could otherwise lead to telomere deprotection and accumulation of DNA aberrations; a hallmark of cancer. To this end, tightly regulated mechanisms exist to ensure high fidelity telomeric replication.